Development of an Inventory Management Information System for a Sock Business Using Google Sheets and AppSheet - ระยับศรี, ทัยชนากร; มูลสาร, ประกาศิต; ศรีเทพ, ธัญลักษณ์; ส่วยสิน, พัชรินทร์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research, entitled “Development of an Inventory Management System for a Sock Retail Business Using Google Sheets and the AppSheet Application,” aimed to design and develop an information system to enhance inventory management efficiency for small and medium-sized enterprises (SMEs) engaged in sock retailing. Due to product variety in terms of colors, sizes, and usage types, along with intense market competition, inventory control processes have become increasingly complex, leading to data inaccuracies and inefficiencies in traditional record-keeping methods.            This study employed a Research and Development (R&D) methodology, including problem and needs analysis, database design using Google Sheets, and application development using AppSheet to support data recording, updating, searching, and reporting of inventory, purchasing, and sales transactions. The sample consisted of 30 participants selected through purposive sampling. A five-level rating scale questionnaire was used to evaluate system efficiency and user satisfaction. Data were analyzed using mean and standard deviation.            The analysis of user satisfaction revealed that, overall, users reported a high level of satisfaction with the system (= 4.41, S.D. = 0.56). When considering each item individually, most aspects were rated at high to very high levels. The highest mean score was for the system’s ability to easily record product data (= 4.50, S.D. = 0.51), followed by the convenience of checking inventory levels (= 4.48, S.D. = 0.51), and the system’s ability to simplify inventory management (= 4.46, S.D. = 0.52).